Substrate Reduction Therapy for Krabbe Disease: Exploring the Repurposing of the Antibiotic D-Cycloserine - LeVine, Steven M.; Tsau, Sheila (Frontiers in Pediatrics, 2022)
Krabbe disease is a lysosomal storage disease that is caused by a deficiency in galactosylceramidase. Infantile onset disease is the most common presentation, which includes progressive neurological deterioration with corresponding demyelination, development of globoid cells, astrocyte gliosis, etc. Hemopoietic stem cell transplantation (HSCT) is a disease modifying therapy, but this intervention is insufficient with many patients still experiencing developmental delays and progressive deterioration. Preclinical studies have used animal models, e.g., twitcher mice, to test different experimental therapies resulting in developments that have led to progressive improvements in the therapeutic impact. Some recent advances have been in the areas of gene therapy and substrate reduction therapy (SRT), as well as using these in combination with HSCT. Unfortunately, new experimental approaches have encountered obstacles which have impeded the translation of novel therapies to human patients. In an effort to identify a safe adjunct therapy, D-cycloserine was tested in preliminary studies in twitcher mice. When administered as a standalone therapy, D-cycloserine was shown to lengthen the lifespan of twitcher mice in a small but significant manner. D-Cycloserine is an FDA approved antibiotic used for drug resistant tuberculosis. It also acts as a partial agonist of the NMDA receptor, which has led to numerous human studies for a range of neuropsychiatric and neurological conditions. In addition, D-cycloserine may inhibit serine palmitoyltransferase (SPT), which catalyzes the rate-limiting step in sphingolipid production. The enantiomer, L-cycloserine, is a much more potent inhibitor of SPT than D-cycloserine. Previously, L-cycloserine was found to act as an effective SRT agent in twitcher mice as both a standalone therapy and as part of combination therapies. L-Cycloserine is not approved for human use, and its potent inhibitory properties may limit its ability to maintain a level of partial inactivation of SPT that is also safe. In theory, D-cycloserine would encompass a much broader dosage range to achieve a safe degree of partial inhibition of SPT, which increases the likelihood it could advance to human studies in patients with Krabbe disease. Furthermore, additional properties of D-cycloserine raise the possibility of other therapeutic mechanisms that could be exploited for the treatment of this disease.